Anthropology, by comparison - Gingrich, André.; Fox, Richard G. (Richard Gabriel), 1939- (London ; New York : Routledge, 2002)
An international group of anthropologists take a fresh look at various neglected approaches to comparison and present new approaches that are relevant to the globalized world of the twenty first century.
Anthropology's comparative consciousness : the case of human rights / Kirsten Hastrup -- Action comparison : efforts towards a global and comparative yet local and active anthropology / James Peacock -- Issues of relevance : anthropology and the challenges of cross-cultural comparison / Marit Melhuus -- Conditions of comparison : a consideration of two anthropological traditions in the Netherlands / Jan J. de Wolf -- Some current kinship paradigms in the light of true Crow Indian ethnography / Emmanuel Désveaux -- Comparison and contextualization : reflections on South Africa / Adam Kuper -- The study of historical transformation in American anthropology / Richard G. Fox -- Comparison and ontogeny / Christina Toren -- The notion of art : from regional to distant comparison / Thomas Fillitz -- When ethnic majorities are 'dethroned' : towards a methodology of self-reflexive, controlled macrocomparison / Andre Gingrich.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Ethnology -- Methodology; Cross-cultural studies; Cross-Cultural Comparison; Ethnologie -- Méthodologie.; Études transculturelles; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Cross-cultural studies; Ethnology -- Methodology; Culturele antropologie; Vergelijkend onderzoek